Balancing the cost of leaving with the cost of living: drivers of long-term retention of health workers: an explorative study in three rural districts in Eastern Uganda. (1st August 2017) - Namusoke Kiwanuka, Suzanne; Akulume, Martha; Tetui, Moses; Muhumuza Kananura, Rornald; Bua, John; Ekirapa-Kiracho, Elizabeth
ABSTRACT: Background : Health worker retention in rural and underserved areas remains a persisting problem in many low and middle income countries, and this directly affects the quality of health services offered. Objective : This paper explores the drivers of long-term retention and describes health worker coping mechanisms in rural Uganda. Methods : A descriptive qualitative study explored the factors that motivated health workers to stay, in three rural districts of Uganda: Kamuli, Pallisa, and Kibuku. In-depth interviews conducted among health workers who have been retained for at least 10 years explored factors motivating the health workers to stay within the district, opportunities, and the benefits of staying. Results : Twenty-one health workers participated. Ten of them male and 11 female with the age range of 33–51 years. The mean duration of stay among the participants was 13, 15, and 26 years for Kamuli, Kibuku, and Pallisa respectively. Long-term retention was related to personal factors, such as having family ties, community ties, and opportunities to invest. The decentralization policy and pension benefits also kept workers in place. Opportunities for promotion or leadership motivated long stay only if they came with financial benefits. Workload reportedly increased over the years, but staffing and emoluments had not increased. Multiple job, family support, and community support helped health workers cope with the costs of living, and holding a secure pensionable government job was valued more highly than seeking uncertain job opportunities elsewhere. Conclusion : The interplay between the costs of leaving and the benefit of staying is demonstrated. Family proximity, community ties, job security, and pension enhance staying, while higher costs of living and an unpredictable employment market make leaving risky. Health workers should be able to access investment opportunities in order to cope with inadequate remuneration. Promotions and leadership opportunities only motivate if accompanied by financial benefits.